De zuigkracht van het medium. Historici als televisiedeskundigen - Tollebeek, Jo (BMGN - Low Countries Historical Review, 2001)
Jo Tollebeek, The power of attraction of the medium. Historians as experts on television.Dutch historians have a long tradition of appearing as experts on television. However, the shape that this 'tele-expertise' has taken has varied greatly since the growth of the medium began in thel950s. Initially, historians presented themselves as authoritative figures who were not afraid to hand down moral judgements on the issues they were discussing. Later on, theyadopted a more reticent approach and strove to project their expertise on the screen in a more businesslike, impartial way. However, developments in this medium forced historians further onto the defensive: as TV experts the historians were in danger of being perceived as 'imagedistorters', rather than as an asset. Only those who succeeded in adapting to the laws of the medium managed to become true 'television personalities'. It was a long haul to get from Lou de Jong to Maarten van Rossem.